1987
DOI: 10.3171/jns.1987.67.5.0657
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral functioning and magnetic resonance imaging findings in young boxers

Abstract: In a prospective investigation of neurobehavioral functioning in young boxers, 13 pugilists and 13 matched control subjects underwent tests of attention, information-processing rate, memory, and visuomotor coordination and speed. The results disclosed more proficient verbal learning in the control subjects, whereas delayed recall and other measurements of memory did not differ between the two groups. Reaction time was faster in the boxers than in the control subjects, but no other differences were significant.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 32 publications
2
21
0
1
Order By: Relevance
“…Levin et al 14 and Jordan and Zimmerman 15 each studied 9 amateur boxers and reported no abnormal MR imaging findings. Jordan and Zimmerman 8 subsequently examined 21 active boxers (16 professional) and 1 retired professional boxer.…”
Section: Discussionmentioning
confidence: 99%
“…Levin et al 14 and Jordan and Zimmerman 15 each studied 9 amateur boxers and reported no abnormal MR imaging findings. Jordan and Zimmerman 8 subsequently examined 21 active boxers (16 professional) and 1 retired professional boxer.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it is one of only nine cohort studies in boxing to have ever been published. [33][34][35][36][37][38][39][40] One of the major advantages of this type of prospective design is the ability to systematically and accurately collect exposure data in the cohort. The high levels of exposure experienced by the boxers indicated that boxing has acute injury rates comparable to, and often lower than, those found in studies of other sports.…”
Section: Discussionmentioning
confidence: 99%
“…Levin et al 50 and Jordan and Zimmerman 51 each studied nine amateur boxers and found no abnormal MRI findings. Jordan and Zimmerman 52 subsequently examined 21 active boxers (16 professional) and one retired professional boxer.…”
Section: "No Clear Relation Betweenmentioning
confidence: 97%